Spatial multi-parameter assessment of rivers water quality in Yogyakarta - Nursetiawan; Wijaya Diva Darma (BIO Web of Conferences)
El Niño-Southern Oscillation (ENSO) affects climate patterns, leading to increased temperatures, high evaporation rates, and reduced precipitation in affected regions. This affects the amount of surface flow that keeps many rivers from moving until they dry up. This is also happened in Winongo, Code and Gajahwong rivers located in Yogyakarta Province. Stagnant water can affect water quality due to immobile water pollution. This study monitors river water quality by assessing Dissolved Oxygen (DO), Potential Hydrogen (pH), and Ferrum (Fe) levels. Water samples were collected from the upstream, midstream, and downstream sections of the Winongo, Code, and Gajahwong rivers to assess water quality. This approach helps identify pollution sources, understand spatial variability, and develop effective water management strategies.. Results indicate that the Winongo River had the highest Dissolved Oxygen (DO) level of 2.4 mg/L in the downstream section. The Code River had the highest pH of 8.1 in the upstream area, while the Gajahwong River showed a stable Iron (Fe) concentration of 2.5 mg/L. According to government regulations, the water quality in all three rivers is suitable only for irrigation purposes.